(untitled) (Swiss Medical Weekly, 2021)
Information on the impact of the COVID-19 pandemic on pregnancy and breastfeeding experiences, as well as on perinatal mental health in Switzerland is limited. In Switzerland, there are few national studies and little information. Using an anonymous online survey accessible after the first wave of the outbreak in Switzerland, we have investigated how this pandemic affected pregnant and breastfeeding women. Among women who completed the survey, 69.0% (1050/1518) indicated the first wave of the pandemic affected their personal habits, 61.0% (689/1131) were affected in their work and 40.0% (632/1573) reported impaired relations with healthcare services (different denominators correspond to the number of participants who answered the question). 36.8% (110/299) of women reported an impact of the pandemic on their current pregnancy experience or breastfeeding experience (8.2%, 46/555). Overall, 11.6% (170/1467) of participants who completed the validated screening tests for mental health symptoms (Edinburgh Postnatal Depression Scale, Generalized Anxiety Disorder 7, Perceived Stress Scale) presented a score compatible with symptoms of major depression, severe anxiety or high perceived stress, which is higher than in the pre-pandemic period according to literature. Risk factors independently associated with impaired mental health were being hospitalized, having symptoms of COVID-19, living with a person with COVID-19 symptoms, having comorbidities, having experienced reduced healthcare services, having restricted usual activities and being a housewife. Protective factors independently associated were a high level of education and living with a partner. Our findings suggest that the COVID-19 pandemic might have significantly affected the well-being and mental health of pregnant and breastfeeding women, directly in the case of exposure, and indirectly as a result of the potential modifications in their life habits and in healthcare facilities.